How to Teach/Learn Praecox Feeling? Through Phenomenology to Medical Education - Gozé, Tudi (Frontiers in Psychiatry, 2022)
Background: The Praecox Feeling (PF) refers to a classical psychopathological concept describing the specific experience of bizarreness arising in the encounter with a person living with schizophrenia spectrum disorders (SSDs). Some studies have shown that experienced psychiatrists take advantage of this experience to perform accurate and rapid diagnostic expertise. It would seem that PF is not contradictory with an operationalized diagnostic approach, but that the PF would intervene at a more tacit level of medical judgment. However, the articulation between the implicit and explicit levels of the psychiatrist's experience in the situation of medical judgment remains little studied, even though it is of crucial importance for structuring the teaching of clinical psychiatry to mental health practitioners. Can diagnostic intuition be learned? Is this experience a kind of "gift" that some may or may not have? Does the PF refer to medical expertise? Methods: To unfold the complexity of his questions this article proposes to conduct an historical, epistemological and phenomenological analysis of the PF. Results: We will first conduct a presentation of historical descriptions of the PF understood as a sensation, intuition and experience, alongside the evolution of the concept of schizophrenia. Then, the article proposes an original phenomenological modelisation of the temporal unfolding of the PF. Discussion: The phenomenological conceptualisation, informed from empirical evidence will try to account for the paradox of the PF as both lived evidence and indescribable experience. PF will be described as a complex cognitive and embodied process based upon ante-predicative aesthetic sensing which is secondly apprehended as perceptible evidence thanks to clinical typification. This conceptualisation relying on Husserl manuscript on intersubjectivity will help to demystify its experiential structure and discuss its relevance for medical education.